Equinodermos (Echinodermata) del Pacífico Mexicano - Honey-Escandón, M. (2008)
Echinoderms (Echinodermata) from the Mexican Pacific. A systematic list of echinoderms of the Mexican Pacific, based on museum specimens of the Colección Nacional de Equinodermos, Instituto de Ciencias del Mar y Limnología, Universidad Nacional Autónoma de México and the National Museum of Natural History, Smithsonian Institution, Washington, D.C., is presented. A total of 196 echinoderm species is recorded, distributed in 112 genera, 56 families and 20 orders. Eight new records for the Mexican Pacific are presented: one for Class Crinoidea: Hyocrinus foelli; six for Class Asteroidea: Echinaster (Echinaster) parvispinus, Henricia nana, Henricia seminudus, Rathbunaster californicus and Leptasterias pusilla, and one for Class Ophiuroidea: Amphiodia tabogae. Rev. Biol. Trop. 56 (Suppl. 3): 57-73. Epub 2009 January 05.